Enjoying Reading: Topics in Youth Literature Published in Croatia 2016 – 2019 - MARTINOVIĆ, Ivana; GRGIĆ, Ivona; Kotromanović, Elizabeta (Anafora, 2023)
This paper consists of a theoretical and empirical part. The theoretical part primarily focuses its attention on the purpose of reading, then discusses the results that the youth from Croatia achieve in international literacy studies and the possible causes of the lack of reading for pleasure among youth. Furthermore, the motives, interests and habits of young people are discussed based on the results of previous research. The authors take the view that the subject of the book is one of the factors that can stimulate and motivate young people to read. The paper further provides an overview of the topics that appear in books intended for young people published from the 60s of the 20th century onwards. The empirical part of the paper presents the results of the research conducted by a combination of different methodological procedures; creating a book list and analyzing the content, with the aim of determining the topics that appear in the books for young people published in Croatia from 2016 to April 2019. The conclusion of the research part of the paper is primarily focused on the topics that are present in the books for youth. The conclusion at the end of the paper brings together insight on the topics of the books for young people and knowledge gained from previous research and theoretical knowledge on reading topics, as well as the tastes, habits and interests of young people to read for pleasure and the role of topics of books in motivating young people for this type of reading.